The Influence of Religiosity, Halal Product Awareness, and Product Trust on Muslim Consumers' Purchase Interest at Waroeng Steak and Shake, Special Region of Yogyakarta. - Shelda Fahriza Shatia; Anas Hidayat (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this study is to determine the relationship and influence between religiosity, halal product awareness, consumer confidence, and purchase intention of Muslim consumers. The information used in this study comes from survey responses distributed to 250 Muslim consumers who have made purchases at Waroeng Steak and Shake Yogyakarta Special Region. Non-probability sampling with a purposive sampling approach is the sampling methodology used in this study. Purposive sampling is used in this study because it is necessary to meet specific criteria before selecting a sample in order to answer certain research questions in addition to providing representative values. Hypothesis testing used in this study uses Structural Equation Modeling (SEM) statistics using the PLS program with the aim of testing the correlation between variables that have been hypothesized in this study. The results of this study indicate that there is an effect of religiosity, halal product awareness, consumer confidence, and buying interest of Muslim consumers.